Studies and Investigations on Various Aspects of Aerobic and Anaerobic Treatments for Sewage and Industrial Effluent - Sunil Jayant Kulkarni; Ajaygiri Kamalgiri Goswami (New Innovations in Chemistry and Biochemistry Vol. 5, 2021)
Oxygen demand of wastewater can be minimized by aerobic and anaerobic treatments. Aerobic treatments include activated sludge process, trickling filters and advance oxidation methods. Higher capital cost for aeration equipment, higher operating and maintenance costs are drawbacks of aerobic methods. Anaerobic treatments have many advantages for treatment of sewage. One of the important methods for the treatment is up flow anaerobic sludge blanket reactors. High conversions and cost effectiveness are advantages of this method. Also high percentage of methane in the generated gas is value addition. Smaller reactor size and lesser biomass production are advantages of anaerobic methods. Presence of oil and grease adversely affect anaerobic treatment. Aerobic treatments are suitable for low organic loading and anaerobic treatments are suitable for very high organic loading. This chapter provides an insight into the research and studies on these treatments.